Description of Bolbolaimus major sp. nov. (Nematoda), from the Yellow Sea, China and phylogenetic analysis in Microlaimidae - Wen, Guo; Huixin, Liang; Yanwei, Lv; Chunming, Wang (Zootaxa, 2023)
Bolbolaimus major sp. nov. is described from Rizhao coast along the Yellow Sea. The new species is characterized by relatively large body size, cuticle strongly annulated, six outer labial sensilla setiform, four cephalic setae long, buccal cavity wide with one large dorsal tooth and two small subventral teeth, amphidial fovea unispiral shaped oval in males and circular in females, spicules curved with swollen proximal end, gubernaculum with anterior-hooked dorso-caudal apophysis, and tail conical with short spinneret. A phylogenetic analysis of maximum-likelihood and Bayesin inference based on rDNA sequences confirms the taxonomic position of Bolbolaimus major sp. nov. within the family Microlaimidae. Tree topology in Microlaimidae shows genus Microlaimus as polyphyletic group and genera in Microlaimidae are closely related.